TI_GERICHTE 52.2021.102 vom 3. Februar 2021 , Licenza edilizia per un'area di carico-scarico con una piattaforma elevatrice - TI Tribunale d'appello (2021)
Licenza edilizia per un'area di carico-scarico con una piattaforma elevatrice